Stephen Biesty's Cross-Sections : Castle - Platt, Richard; Illustrated by Biesty, Stephen (London Dorling Kindersley, 1994)
Shows the structure of a castle and its defenses under siege. Examines life at all levels within the castle. Suggested level: intermediate, secondary.
Include Color Illustrations, Glossary and Index.
Keywords: Castles -- Civilization, Medieval